"A good hell": absurdist insights for environmental education & research. Issue 4 (3rd April 2023) - Lowan-Trudeau, Greg
Abstract: In this inquiry, I explore, expose, and extrapolate upon sociopolitical and environmental absurdism as an environmental academic and educator based in Alberta, Canada—a well-known, and somewhat infamous, centre of oil and gas production and energy development in general. Moving beyond Alberta as a catalytic example, I introduce and discuss various forms of and themes within absurdist literature, theatre, and activism. In closing, I consider the theoretical and pedagogical potential of absurdism for environmental education scholarship and practice.